2020
DOI: 10.1002/1873-3468.13899
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic cleavage of Trop2 at Arg87 is mediated by matriptase and regulated by Val194

Abstract: Proteolytic processing is an important post-translational modification affecting protein activity and stability. In the current study, we investigate the N-terminal cleavage of Trop2, a protein which is overexpressed in many cancers. We demonstrate that Trop2 is cleaved at Arg87 by a transmembrane serine protease, matriptase. Homology modeling and site-directed mutagenesis of amino acids in close proximity to the matriptase cleavage site reveal the importance of Val194 in regulating Trop2 cleavage. Co-immunopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Tumor-specific proteolytic cleavage of TROP-2 occurs at the conserved cleavage site R87-T88 of the TY loop, which is similar to that of EpCAM at the typical dibasic site R80-R81 ( Kamble et al., 2020 ; Pavšič et al., 2014 ; Trerotola et al., 2021 ; Wu et al., 2017 ). Proteolytic cleavage activates the cell-growth stimulatory properties of TROP-2 ( Trerotola et al., 2021 ).…”
Section: Discussionmentioning
confidence: 93%
“…Tumor-specific proteolytic cleavage of TROP-2 occurs at the conserved cleavage site R87-T88 of the TY loop, which is similar to that of EpCAM at the typical dibasic site R80-R81 ( Kamble et al., 2020 ; Pavšič et al., 2014 ; Trerotola et al., 2021 ; Wu et al., 2017 ). Proteolytic cleavage activates the cell-growth stimulatory properties of TROP-2 ( Trerotola et al., 2021 ).…”
Section: Discussionmentioning
confidence: 93%
“…Mapping of proteolytic cleavage sites reported in the literature reveals that all are at least partially accessible in Trop2 dimer ( Figure 4 c,d). First, the matriptase cleavage site at surface-exposed R87 [ 20 , 44 ] is located within the TY-loop, similarly as the equivalent matriptase cleavage site in EpCAM (R80–R81; Figure 1 ) [ 6 , 45 ]. Although the TY-loop is part of the dimer interface, the structural plasticity described above may (via temporal TY-loop disengagement from juxtaposed βCD) enable efficient cleavage by enhancing the accessibility of the cleavage site.…”
Section: Resultsmentioning
confidence: 99%
“…Although the TY-loop is part of the dimer interface, the structural plasticity described above may (via temporal TY-loop disengagement from juxtaposed βCD) enable efficient cleavage by enhancing the accessibility of the cleavage site. Interestingly, it was shown that mutation V294A (part of the βCD, shown in orange in Figure 4 c) prevents matriptase cleavage at R87 without affecting the Trop2 dimerization, and the observed effect was attributed to impaired binding of matriptase to the Trop2 as the substrate [ 44 ]. Since in our crystal structure side chains of V194 and the nearby V191 are both located on the opposite side of βCD than the juxtaposed TY-loop and are therefore not exposed, it is likely that side chain of V194 is not directly involved in matriptase interaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human specimen collection methods were performed in accordance with relevant national and EU directives and regulations. The study was approved by the Ethics Committee of the Third Faculty of Medicine of Charles University in Prague (ref. 26/2014 and 01/2020).…”
Section: Methodsmentioning
confidence: 99%